Pattern of Thyroid Dysfunction in Women with Menstrual Disorders - Khatiwada, Saroj; Gautam, Sharad; KC, Rajendra; Singh, Shruti; Shrestha, Shrijana; Jha, Punam; Baral, Nirmal; Lamsal, Madhab (Annals of Clinical Chemistry and Laboratory Medicine, 2016)
BACKGROUND Thyroid disorders are among the commonest endocrine disorders worldwide. Thyroid dysfunction can interfere in multiple metabolic and physiological processes including menstrual cycle. This study was conducted to find pattern of thyroid dysfunction among women with menstrual disorders. METHODS Two hundred thirty three females with menstrual disorders were screened for thyroid dysfunction. Thyroid function was assessed by measuring serum free triiodothyronine (T3), free thyroxine (T4) and thyroid stimulating hormone (TSH) levels. RESULTS The mean age of study patients was 25.7±6.8 years. The most common menstrual disorder observed was irregular cycle (72.5%, n=169) followed by amenorrhea (21.9%, n=51) and menorrhagia (5.6%, n=13). Most of the patients were in the age group 15-24 years (51.1%, n=119), followed by 25-34 years (36.1%, n=84) and 35-45 years (12.9%, n=30). Mean level of free T3 and T4 was 2.91±1.05 pg/ml, 1.42±0.57 ng/dl respectively. Median TSH was 2.0 mIU/L (IQR, 1.0-4.0). Thyroid dysfunction was seen in 25.8% (n=60) women. Most common thyroid dysfunction was subclinical hypothyroidism (14.2%, n=33) followed by subclinical hyperthyroidism (6.9%, n=16), overt hyperthyroidism (3%, n=7) and overt hypothyroidism (1.7%, n=4). CONCLUSIONS The study finds thyroid dysfunction especially subclinical hypothyroidism to be common among women with menstrual disorders. Thus, it may be beneficial to screen menstrual disorder patients for thyroid function especially to rule out thyroid disorder as potential etiological agent for menstrual disturbance.